2010
DOI: 10.1177/1077559510367939
|View full text |Cite
|
Sign up to set email alerts
|

Risk Reduction for Substance Use and Trauma-Related Psychopathology in Adolescent Sexual Assault Victims: Findings From an Open Trial

Abstract: Limited attention has been paid to the development and evaluation of interventions that reduce risk for substance use, while also targeting trauma-related psychopathology among maltreated adolescents. Risk Reduction through Family Therapy (RRFT) is a multi-component treatment that integrates principles and interventions from existing empirically supported treatments. The purpose of the current study was to evaluate the feasibility of implementation and initial efficacy of RRFT through an open pilot trial invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 21 publications
0
53
0
Order By: Relevance
“…The five 526,533,621,673,678 studies examined family or multisystemic therapies. The Conran and Love 621 study was a case study, the Costa et al 678 study was an action research project, and the studies by Danielson et al 526 Tjersland et al 673 and Woodworth 533 were uncontrolled studies (see Table 17).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The five 526,533,621,673,678 studies examined family or multisystemic therapies. The Conran and Love 621 study was a case study, the Costa et al 678 study was an action research project, and the studies by Danielson et al 526 Tjersland et al 673 and Woodworth 533 were uncontrolled studies (see Table 17).…”
Section: Methodsmentioning
confidence: 99%
“…Five 526,533,621,673,678 very different studies addressed issues of the acceptability of systemic interventions. Details of these studies can be found in Table 17.…”
Section: Systemic Interventionsmentioning
confidence: 99%
See 3 more Smart Citations